Oxtoby Spaces, Pseudocompleteness, and Hyperspaces - Flores-González, Mario; Maya, David; Orozco-Zitli, Fernando; Pichardo-Mendoza, Roberto (Topology Proceedings, 2022)
The subclasses of all O-pseudocomplete spaces, of all T-pseudocomplete spaces, and of all Oxtoby spaces of the class of Baire spaces are considered. Additionally, the relation between a space belonging to such a subclass and its hyperspaces belonging in the same subclass are studied.